Enzymatic treatment in improving nutritive value of local brown rice for poultry feed - Mustapha, Nurul Asyifah (2012)
Malaysian poultry industry depends heavily on expensive imported feed materials like soybean and maize. Local brown rice is a potential feed ingredient to replace these imported feeds. It is produced locally, easily available and low in production cost. Brown rice composed of nutrients required by poultry such as protein, carbohydrates and fats. However, it may also contain anti-nutrients that cause adverse effects to poultry performance. In this study, brown rice varieties MR239 and MR257 were investigated for their nutrients, anti-nutritional factors mainly non-starch polysaccharides (NSP) and its true metabolisable energy (TME) value. The enzymatic hydrolysis was carried out with the aim of eliminating the NSP and further optimize for production of hydrolyzed brown rice. The effects of enzyme supplementation were evaluated through true metabolisable energy (TME) value of poultry. The composition of both varieties showed that they contained nutrient as required by the poultry such as protein content of 9.0% and 8.8%, carbohydrates contents of 87.6% and 87.7% for MR239 and MR257, respectively and balanced amino acids. The energy value of both varieties were also high represent by gross energy of 16.0 MJ/kg and 15.9 MJ/kg and also TME value of 12.2 MJ/kg and 15.5 MJ/kg for MR239 and MR257,respectively. The NSP was present in small amount as compared to other types of feedstuffs such as wheat and barley which represent by cellulose 1.6% and 0.1%, hemicelluloses 4.3% and 2.0%, arabinoxylan 0.042% and 0.03% and also β-glucan 0.2% and 0.3% for MR239 and MR257, respectively. The application of enzymes by enzymatic hydrolysis showed that xylanase, cellulase and β- glucanase were able to degrade the fibrous fraction of NSP in brown rice. The optimization of enzymatic hydrolysis condition was carried out using these three enzymes with activity range from 1 – 3 U/mL, temperature from 30 - 50°C, pH of 4 - 6 and substrate concentration of 5 – 15% w/v. The range of each factor was set based on preliminary experiment. The significant factors screened using twolevel factorial design was temperature, pH, substrate and cellulase activity. These parameters were optimized by central composite design and produced optimal value of pH 4.5, temperature of 40°C, 12.5% w/v of substrate concentration and 2 U/mL of cellulase activity. Hydrolyzed brown rice was produced based on these optimized conditions. The effectiveness of enzymes supplementation was evaluated by determination of chemical composition and conducted the force feeding experiment for TME value. The composition of hydrolyzed brown rice has shown the improvement in the nutrients content by increase in protein content as 11.2%, fat as 2.7% and also the reduction in NSP components to 3.0% cellulose, 1.3% hemicelluloses, 0.4% β-glucan and 0.05% arabinoxylan after enzymatic hydrolysis process. The energy value has been increased for hydrolyzed brown rice. The TME value of hydrolyzed substrate was 16.1 MJ/kg as compared to TME of untreated brown rice which was 13.9 MJ/kg. Local brown rice MR239 and MR257 that were not suitable for human consumption was selected for poultry feed as it has potential to replace the imported feed. The results showed the nutritive values of brown rice were improved with the treatment of enzymes.